Biologists, policymakers and other specimens: A story about collecting, regulating and social interactions (2016)
Abstract: This document is a story of the regulation of the practices of biology in Colombia. It unfolds, mainly, in the first decade of this millennium and it is constructed by exploring different specimens that inhabit quite different ecosystems in this sociotechnical controversy: News, videos, letters, conversations, scientific articles, forums and even fictional situations. This story of regulation of science has a “happy end”, or, a victory for the community of biologists when were published by Ministry of Environment the Decrees 1375 and 1376, in 2013, which regulate the practice of collecting biological specimens for scientific purposes and the biological collections. But before a process of policymaking was performed with a relevant participation of biologists, it was necessary to configure a problematic situation, full of associations which help scientists to mobilize the needed resources for promoting a change in the normativity that regulates their practices. While constructing this story, a constant parallelism between the “world of biology” and the process of doing research of communities of biologist is done, generating a thesis that does not only talk about a change in the regulatory framework of biology but about doing collecting and analysing work for the understanding of a scientific community.